Determination of Norepinephrine Using a Glassy Carbon Electrode Modified with Graphene Quantum Dots and Gold Nanoparticles by Square Wave Stripping Voltammetry - Segura-Segura, R; Segura-Segura, R; Pizarro-Reyes, J; Pizarro-Reyes, J (Springer Netherlands, 2019)
In this work, a glassy carbon electrode modified with graphene quantum dots and gold nanoparticles (GCE/GQDs/AuNPs) was developed for norepinephrine (NE) determination using squarewave stripping voltammetry. GQDs were synthesized by citric acid pyrolysis and characterized by UV–Vis and fluorescence spectroscopy. The chemically synthesized AuNPs were characterized by transmission electron microscopy and UV–Vis spectroscopy (Plasmon Band). GCE/GQDs surface was characterized by Raman spectroscopy and scanning electron microscopy. The conditions for the determination of NE with GCE/GQDs/AuNPs were optimized. The linear range was observed between 0.5 and 7.5 µmol L −1 , with a detection limit (LOD) of 0.15 µmol L −1 . The proposed methodology was validated with spiked samples for good precision and accuracy. GCE/GQDs/AuNPs were used in pharmaceutical preparations (NE ampoules) and in rat brain tissue with satisfactory results. Graphical abstract: [Figure not available: see fulltext.]. © 2019, Springer Nature B.V.